DETERMINAN KUALITAS INFORMASI LAPORAN KEUANGAN PEMDA KABUPATEN MALAKA - Baso, Susana Purnamasari; Betu, Kristina Wada (AKSIOMA : Jurnal Manajemen, 2023)
The purpose of this study was to determine the factors that influence the quality of financial reporting information for the local government of Malacca Regency. This is because the quality of financial information will greatly determine decisions and describe the quality of the financial managers themselves. The variables used in this study are human resources, technology utilization, internal control systems and the quality of financial reports. The hypothesis in this study is that human resources, technology utilization and internal control systems have a partial and significant effect on the quality of financial reports. In this study, the questionnaire section was used in the data collection method. The sample in this study amounted to 155 employees within the scope of the Regional Work Unit of the Malacca Regency Government. The results of this study prove that human resources, the use of information technology significantly affect the quality of financial statement information with a significance level of 0.002 and 0.10. Meanwhile, internal control has no effect on the quality of financial reporting information. The contribution of human resource variables, control systems, use of technology to the quality of financial reports is 56.7%.